VIOLENCE AGAINST WOMEN WITH DISABILITIES (Annual of the Faculty of Philosophy in Skopje, 2024)
The UN Convention on the Rights of Persons with Disabilities (CRPD) withits Optional Protocol is the first binding legal act and leading international instrumentregarding the rights of persons with disabilities. One of the principles of CRPDis “respect for inherent dignity, individual autonomy including the freedom to makeone’s own choices and independence”, whereby persons with disabilities are recognizedas holders of rights taking into account their specific situation. CRPD recognizes inArticle 6 that “women and girls with disabilities are subject to multiple discrimination”and mandates signatory countries to “take measures to ensure their full and equalenjoyment of all human rights and fundamental freedoms.” The research was done inorder to examine the readiness of the state to institutionally cover the awareness of girlsand women with disabilities, their education on the issue of violence, access to servicesand information appropriate to the needs of each category separately, as well as systemicsolutions for their protection from violence. A qualitative research strategy was applied,and the research was conducted with representatives of the Centers for Social Work, representativesfrom the Ministry of Labor and Social Policy, professionals who are directproviders of services in the field of non-family protection, as well as the girls and womenwith disabilities themselves. The main conclusions that emerge from the research saythat girls and women with disabilities are more susceptible to violence, especially bytheir partners or family members. More awareness is needed to recognize and encouragereporting of violence.
Keywords: violence; girls and women with disabilities; victims of violence